VOLUME PENOTOLAN MEMPENGARUHI FINGERPRINT EKSTRAK METANOL HERBA SAMBILOTO (ANDROGRAPHIS PANICULATA (BURM. F.) NEES) DENGAN KLT-SPEKTROFOTODENSITOMETRI - Ugrasena Putu Yudha; Puspita Sari Dyah Ratna Ayu; Kumara Dewi Ni Wayan Rika (Institut Teknologi dan Kesehatan Bintang Persada, 2023)
Spotting volume is an important factor affecting the resolution value of the chromatogram, the number of peaks and separation, peak profile and peak broadening, as well as the asymmetry of the peaks. This study aims to determine the effect of bottling volume on fingerprint chromatography of the methanol extract of Andrographis paniculata (Burm. F.) Nees herb and to determine fingerprint chromatography at optimum volume. The chromatographic system used refers to the Indonesian Herbal Pharmacopoeia. Sambiloto herbal samples were spotted with a variety of 3 µL bottling volumes; 5µL; 10µL; 15µL; 20 µL and 25 µL on a 60 GF254 silica gel plate were then eluted with a mixture of chloroform P and methanol P (9:1) v/v. The plates were scanned with a TLC Scanner 3 (CAMAG) at a wavelength of 210 nm. Spectra were made for each spot at a wavelength of 190-400 nm. Parameters that were calculated were resolution values, tailing factor from andrographolid peaks, and cosine functions (C) from volume variation chromatograms to determine the effect of spotting volume. The bottling volume selected from the optimization step was 5 µL with andrographolid peak resolution with the previous and following peaks being 1.57 and 1.16, respectively. The tailing factor value was 1 and the number of peaks that appeared was 10. The average value of C in the 5 µL bottling volume precision test was 99.36 with a VC of 1.17% (VC <2%)